2004
DOI: 10.1007/s00216-003-2446-4
|View full text |Cite
|
Sign up to set email alerts
|

A mini-review of mass spectrometry using high-performance FTICR-MS methods

Abstract: Structural characterization of macromolecules is currently delivering new insights into the behavior of individual molecules or molecular ensembles. Technological advances have made it possible to examine smaller and smaller amounts (down to single molecules) of larger and larger molecular systems. Mass spectrometry in particular is capable of the detailed study of extremely small quantities (down to a single molecule) of very large (biological) molecules. The advent of new ionization techniques such as electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 108 publications
0
32
0
Order By: Relevance
“…While the TOF/TOF experiments were useful in the identification of native Litset Pen4−1, advances in peptide fragmentation have been reported that hold promise for the intact analysis of penaeidins [64][65][66][67]. One of these technologies is electron capture dissociation (ECD) in conjunction with Fourier transform ion cyclotron resonance mass spectrometry (FTICR MS) [66,68,69].In an effort to further explore MS/MS approaches for fragmentation of intact penaeidins, FTICR MS in combination with ECD was used to generate fragments of the full-length Litset Pen3−4 without prior reduction of the disulfide bonds (Fig. 5).…”
mentioning
confidence: 99%
“…While the TOF/TOF experiments were useful in the identification of native Litset Pen4−1, advances in peptide fragmentation have been reported that hold promise for the intact analysis of penaeidins [64][65][66][67]. One of these technologies is electron capture dissociation (ECD) in conjunction with Fourier transform ion cyclotron resonance mass spectrometry (FTICR MS) [66,68,69].In an effort to further explore MS/MS approaches for fragmentation of intact penaeidins, FTICR MS in combination with ECD was used to generate fragments of the full-length Litset Pen3−4 without prior reduction of the disulfide bonds (Fig. 5).…”
mentioning
confidence: 99%
“…MMA of these instruments is approximately 1 ppm, surpassing ion-traps by at least 2 orders of magnitude, and resolution can be routinely 100000. FTICR analysers are highly versatile and can be combined with both MALDI and ESI [20,21] ion sources. The extremely high mass resolution/MMA makes FTICR-MS the instrument of choice for studying protein isoforms [22] (and see below).…”
Section: Principles and Instrumentationmentioning
confidence: 99%
“…The principle underlying FTICR mass spectrometry forms the basis of its unique capabilities. There have been a couple of excellent reviews [25][26][27][28] that give very detailed descriptions of this technique, therefore only the very fundamentals are briefly described herein. FTMS uses the ICR principle to determine m/z values of ions, whereby ions are trapped in a cell that is located within a static magnetic field (Figure 1).…”
Section: Fourier Transform Ion Cyclotron Resonance (Fticr) Mass Spectmentioning
confidence: 99%